PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM - Bahri, Syaiful (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2018)
The purpose of this research is to know influence of earning per share (EPS),price earning ratio (PER), debt to equity ratio (DER), return on assets (ROA) andreturn on equity (ROE) to stock price. Research population of food and beverage subsector listed on Indonesia Stock Exchange 2014-2016. Samples of research withpurposive sampling as many as 11 companies.  The results of research EPS, PER, DER has no effect on stock prices. ROA andROE affect the stock price of companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange.